Strategi Guru Dalam Membimbing Karakter Gotong Royong Pada Peserta didik Kelas V B di SDN 74 Kota Bengkulu - Ermala Aweni; Irma Yani Agustin; Zuliha Nuramin Nanti; Dea Kartika (Yayasan Darusssalam Bengkulu, 2024)
Abstract: Mutual cooperation learning together is a relationship between one individual and another individual to create cooperation in solving problems that will be of mutual interest so as to create a sense of togetherness. The aim of the research is to describe teachers' strategies in guiding students' mutual cooperation character and describe the obstacles teachers face in guiding students' mutual cooperation character. The research used qualitative methods and the research subjects consisted of the principal, class teacher, and 27 students out of 12 students and 15 female students. Data collection techniques include observation, interviews and documentation to answer questions, namely what strategies are applied when guiding students and what obstacles are faced by class V B students in Bengkulu City? The results obtained show that the teacher has succeeded in implementing the character of mutual cooperation with students so that students carry it out with full agreement and without compulsion which can create self-awareness for working together in learning together among students. The teacher's strategy in guiding the character of mutual cooperation is by being a direct example, forming group discussions, making rules according to mutual agreement, and carrying out activities together.